2008
DOI: 10.1590/s0004-27302008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da lipodistrofia associada ao HIV em pacientes ambulatoriais brasileiros: relação com síndrome metabólica e fatores de risco cardiovascular

Abstract: RESUMOA lipodistrofia associada ao HIV (LAHIV) acomete 40% a 50% dos pacientes infectados pelo vírus, mas sua prevalência no Brasil é desconhecida. O objetivo deste trabalho foi avaliar a prevalência de LAHIV entre adultos brasileiros infectados, bem como sua relação com fatores de risco cardiovascular e sín-drome metabólica (SM). Foram avaliados 180 pacientes maiores de 18 anos, infectados por HIV, atendidos no Ambulatório de Infectologia da Universidade Estadual de Londrina. Por meio de entrevista e revisão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
2
28

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 32 publications
7
35
2
28
Order By: Relevance
“…In an article by Soares et al 26 with 227 PLWHA, the prevalence of lipodystrophy found through subjective method was 40%, the highest prevalence was observed among women (44 versus 38.8%), as observed in our study (56.5 versus 48.6%). On the other hand, Diehl et al 13 found a higher prevalence of lipodystrophy among men (68 versus 46%), as observed here by the FMR index.…”
Section: Rev Bras Epidemiol Jul-set 2017; 20(3): 526-536supporting
confidence: 78%
See 1 more Smart Citation
“…In an article by Soares et al 26 with 227 PLWHA, the prevalence of lipodystrophy found through subjective method was 40%, the highest prevalence was observed among women (44 versus 38.8%), as observed in our study (56.5 versus 48.6%). On the other hand, Diehl et al 13 found a higher prevalence of lipodystrophy among men (68 versus 46%), as observed here by the FMR index.…”
Section: Rev Bras Epidemiol Jul-set 2017; 20(3): 526-536supporting
confidence: 78%
“…A research carried out in Brazil, by Diehl et al, evaluated 180 HIV carriers older than 18 years of age through subjective method and found a prevalence of 55% of HIVLS. However, the authors observed, through clinical data, that 73% of those assessed had some kind of body fat, though only 76% of these individuals reported such alteration 13 . Due to the fact that alterations in body fat distribution and lipid and glucose metabolism significantly increase morbidity and mortality of PLWHA in HAART, it is essential to early identify the risk for cardiovascular diseases development.…”
mentioning
confidence: 96%
“…Analisando especificadamente a presença ou não da lipodistrofia, nota-se que a Síndrome Lipodistrófica pode estar associada com o tempo de infecção e tempo de terapia antirretroviral 26,27 . Diante disso, o estudo em questão também notou que os pacientes com lipodistrofia apresentavam taxa metabólica basal menor e com tempo de infecção pelo HIV e uso da TARV por maior tempo (p<0.05).…”
Section: Discussionunclassified
“…A maior utilização, neste estudo, dos esquemas de TARV com inibidores de transcriptase reversa análogos de nucleosídeos vai ao encontro do estudo de Diehl et al 27 e Tsuda et al 31 , que tanto pacientes com lipodistrofia como sem foram os medicamentos predominantes, bem como, o esquema predominante nos estudos e neste foi o AZT/3TC/ EFV (47,30%). Além do mais, ressalta-se a não associação da utilização de inibidores de protease com a lipodistrofia neste estudo.…”
Section: Discussionunclassified
“…The prevalence of lipodystrophy in any of the three forms of manifestation (lipoatrophy, lipodystrophy or mixed) is not well established in the literature. The fact that there is no consensus on the diagnostic method and the differences in the studied populations may account for variation between studies [19][20][21][22] . In a review by Tien and Grunfeld 23 , several studies on lipodystrophy were analyzed, which reported that the rates of lipodystrophy range from 30% to 62%.…”
Section: Discussionmentioning
confidence: 99%